Handgrip Strength as a Useful Marker of Nutritional Status Assessment in Cirrhotic Patients - Rema, Robert; Parveen, Shohely; Rahman, Mohammad Asadur; Rahman, Md Zahidur; Safiullah, A B M; Chowdhury, Mohammad Shoaib; Ahmed, Dewan Saifuddin (Faridpur Medical College Journal, 2026)
Background: Protein energy malnutrition is a recognized feature of cirrhosis of liver. Anthropometric measures such as body mass index (BMI), mid arm circumference (MAC), triceps skin fold thickness (TSFT) and subjective global assessment (SGA) have some limitations in assessment of malnutrition. The objective of this study was to assess the efficacy of hand grip strength in nutritional assessment of cirrhotic patient and its sensitivity and specificity in detecting malnutrition. Materials and methods: This was a cross sectional observational study conducted in the Department of Gastroenterology, BSMMU, Shahbag, Dhaka, during the period September 2018 to August 2019. In total of one hundred and thirty (130) eligible patients more than 18-year-old, diagnosed as cirrhosis of liver were enrolled. Results: Out of one hundred and thirty (130) cirrhotic patients, there were 62.3% (81) malnourish according to SGA rating, where 37.7% were moderately malnourish and 24.6% patients were severely malnourished. HGS had the highest area under curve 0.84 (95% confidence interval (CI) 0.77–0.91, P=0.001) compared to MAC 0.80 (95%CI 0.72–0.87, P=0.001) and TSFT 0.75 (95% CI 0.66–0.83, P=0.001) for assessing malnutrition. In comparison of HGS, TSFT and MAC, the sensitivity was 75.5%, 53% and 71%, respectively. The Specificity was 88.9%, 87% and 75% respectively and diagnostic accuracy was 89%, 87% and 82% respectively in assessing malnutrition. Conclusion: HGS is a simple, bed side tool that can be used to assess the muscle status and can be used in a complementary manner with other methods for proper assessment of the patients. Faridpur Med. Coll. J. 2026;21(1):30-37